Surface Complexation of Chromium(VI) on Iron(III) Hydroxide: Mechanisms and Stability Constants of Surfaces Complexes - Mhamed Hmamou; Fatima Ezzahra Maarouf; Bouchaib Ammary; Abdelkebir Bellaouchou (Universitas Gadjah Mada, 2021)
The adsorption of chromate ions H2-yA (y = 1, 2, and A = CrO42–) on iron(III) hydroxide was conducted as a function of adsorbent mass, solution pH, and hydration time. The surface complexation technique, based on the examination of the chromate distribution between the solid and liquid phases, was adopted to predict the adsorption mechanism. To specify stoichiometry of the chromate surface complexes, the proton (n > 0), and hydroxyl (n < 0) ion-exchange was evaluated at a pH range of 2–12. The obtained “n” values are ranging between -1 and 1. As a result, the sorption process involved specific chemical interaction with surface sites, resulting in 1H+ and 1OH– release of the adsorbate molecule. The surface species identified were ; ; ; ; ; ; ; and . The logarithmic values of their complexing constants were: log K00 = 1.81 ± 0.04; log K11 = -3.53 ± 0.07; log K21 = -1.03 ± 0.23, log K1-1 = 7.15 ± 0.14 and log K2-1 = 9.62 ± 0.53. The results showed that the chromate adsorption on Fe(III) hydroxide was of electrostatic and chemical nature at pH lower than 5.5, and only of chemical nature at pH superior to 5.5. Taking into account these considerations, Fe(III) hydroxide could be considered an excellent sorbent for the removal of Cr(VI) from wastewater solutions.